Jak je vnímán význam paliativní péče a spolupráce s paliatry z pohledu českých onkologů? (Paliativní medicína, 2024)
Abstract: As part of the cooperation between the Supportive Care Group and the Psycho-Oncology Group of the Czech Oncology Society and the Czech Society of Palliative Medicine, we initiated the Survio 2024 (www.survio.com) electronic questionnaire, which included a total of 8 questions for clinical oncologists, hemato-oncologists and radiation oncologists, and which was available on 29.3.-31.5.2024. A total of 49 respondents completed the questionnaire. The evaluation of cooperation and palliative care in oncology can be considered positive. An interesting finding is that, compared to international and national recommendations, the initiation to the correct timing of the integration of palliative care is still significantly later. Also public education in the perception of palliative medicine and care will certainly be necessary, as well as active support for its accessibility. It can be assumed that the focus of educational activities among oncologists could also further contribute to further deepening of mutual cooperation and greater inclusion of aspects of palliative medicine in the comprehensive care of cancer patients.
Keywords: Questionnaire